Effect of cellulose additive on the silicon carbide film by decomposition and conversion of silicon nitride. Issue 6 (15th April 2020) - Chen, Song; Chen, Changlian; Liang, Xin; Wu, Changsheng; Ji, Jiayou; Xu, Man; Zhang, Zhanhui; Huang, Zhiliang
Abstract: Using silicon nitride (Si3 N4 ) as raw material and cellulose as an additive, dense silicon carbide (SiC) film was successfully prepared on the surface of the graphite matrix by the decomposition and conversion of Si3 N4 . Scanning electron microscopy, X-ray energy dispersive spectroscopy and X-ray diffraction were used to characterize the microstructure, the composition, and the crystal phase of SiC film. The effect of the cellulose additive on the grain morphology of SiC film and the mechanism were studied. The results show that the evaporation and conversion of silicon nitride at the high temperature is an efficient method for depositing SiC film on the surface of the graphite matrix. The addition of cellulose is helpful to the bridge of membrane particles and can change the morphology and size of SiC grains. With the increase of cellulose content, the size of SiC grain decreased, but the thickness of film increased first and then decreased. When the cellulose content was 20 wt%, the grains on the SiC film surface were uniform and closely packed, and the thickness of SiC film on graphite matrix is up to 107.6 μm.